DESIGNING FABRICS FOR A GIVEN STRETCHABILITY - KHAMRAEVA , SITORAKHON; КADIROVA DILFUZA; DAMINOV, ASKARALI (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
The article presents the results of determining the geometric parameters of the fabric design method for a given stretchability. While studying literary and analytical studies, it was found that fabrics containing elastomers are very popular with consumers. In literary sources, there are practically no recommendations on the technology of manufacturing stretchable fabrics. The properties of stretchable yarns differ significantly from the properties of traditional yarns used in weaving. Therefore, it is necessary to identify the range of technological weaving modes in which it is possible to obtain stretchable blended fabrics with the inclusion of elastane yarns. The productivity of equipment and labor and the quality of manufactured products depend on the correctly selected technological parameters. The results of the study show that the optimal machine parameters are established mainly empirically, sometimes with the help of experimental studies, and for the experimental fabric they are individual. However, there are general patterns or initial prerequisites that must be taken into account when developing the optimal parameters